Willingness to Receive COVID-19 Vaccine and Associated Factors Among College Students in Gondar City, Northwest Ethiopia - Aklil, Mastewal Belayneh; Temesgan, Wubedle Zelalem; Gessesse, Dereje Nibret; Kassa, Bekalu Getnet; Tiguh, Agumas Eskezia; Kebede, Azmeraw Ambachew; Ayalew, Minychil Demelash; Yismaw, Ayenew Engida (Frontiers in Education, 2022)
Background: The increasing incidence of coronavirus disease 2019 (COVID-19) continues to cause morbidities and mortalities, and economic crises worldwide. College students are among the high-risk groups to acquire the disease for many reasons. Thus, the COVID-19 vaccine is the most effective and safe method to control this deadly disease. Although World Health Organization advocates vaccination is the best approach to tackle COVID-19, refusal of vaccination is a global problem. Evidence reaching out to college students is scarce in Ethiopia, particularly in the study area. Therefore, this study aimed to assess willingness to receive the COVID-19 vaccine and associated factors among college students in Northwest Ethiopia. Methods: An institution-based cross-sectional study was conducted among 626 participants from January 12 to 26, 2021. Data were collected using a pre-tested, self-administered questionnaire, and a multistage sampling technique was used. Data were entered into EPI info version 7.1.5.2 and exported into SPSS version 20 for analysis. Both bivariable and multivariable logistic regression analyses were employed to identify associated factors. The level of significance was determined based on a p-value < 0.05. Results: In this study, the student’s willingness to receive COVID-19 vaccine was 34.2% (95% CI: 30.9-38.1). Being third year student (AOR = 1.88; 95% CI: 1.27-2.77), being male (AOR = 1.45; 95% CI: 1.02-2.09), being married (AOR = 2.07; 95% CI: 1.28-3.33), ever watching TV (AOR= 0.39; 95% CI: 0.24-0.65), and having a positive attitude towards COVID-19 prevention (AOR = 2.33; 95% CI: 1.61-3.39) were the factors significantly associated with willingness to receive the COVID-19 vaccine. Conclusion: Willingness to receive the COVID-19 vaccine among college students was low. Sensitization of students about COVID-19 vaccine safety and effectiveness before directly giving the vaccine is recommended. Moreover, concerned bodies better give health education to students to bring a positive attitude towards the COVID-19 vaccine.